Strategic land use optimization in tsunami-prone city of Banda Aceh: Building disaster awareness and resilience - Irwansyah, Mirza; Achmad, Ashfa; Manaf, Asnawi; Hanifah, Winda (Edelweiss Applied Science and Technology, 2025)
Banda Aceh, the capital city of Aceh Province, is located at the northern tip of Sumatra Island. Geographically, it is particularly vulnerable to earthquakes and tsunamis. In 2004, a devastating earthquake struck the city, leading to a tsunami that destroyed and washed away many developed urban areas. Over the last decade, rapid development has significantly transformed the city's landscape. As reconstruction efforts continue, it is essential that they adhere to Banda Aceh’s Spatial Planning, especially considering the region's susceptibility to disasters due to past tsunami events. This study aims to identify and analyze the tsunami-vulnerable regions in Banda Aceh resulting from the 2004 disaster, assess the spatial planning from 2009 to 2029 in these areas, and propose alternative safe zones for tsunami preparedness. The mixed-method approach employs scoring analysis, GIS software, and interviews with local residents and relevant agencies. The findings indicate that the tsunami inundation zones include the districts of Syiah Kuala, Meuraksa, Kutaraja, Jaya Baru, and Kuta Alam. Post-tsunami land use in Banda Aceh has evolved significantly, with vacant land decreasing from 2,519.2 hectares in 2005 to 341.55 hectares in 2014. Three alternative tsunami-safe zones are proposed, with the safest being parts of Jaya Baru, Kuta Alam, and Syiah Kuala districts.